2016
DOI: 10.1186/s12890-016-0267-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of lipocalin-2 and syndecan-4 levels to differentiate bacterial from viral infection in children with community-acquired pneumonia

Abstract: BackgroundIn this study, we evaluated the lipocalin-2 (LIP2) and syndecan-4 (SYN4) levels in children who were hospitalized for radiologically confirmed CAP in order to differentiate bacterial from viral infection. The results regarding the LIP2 and SYN4 diagnostic outcomes were compared with the white blood cell (WBC) count and C reactive protein (CRP) levels.MethodsA total of 110 children <14 years old who were hospitalized for radiologically confirmed CAP were enrolled. Serum samples were obtained upon admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
1
26
2
1
Order By: Relevance
“…The conflicting difference between higher syndecan-4 levels in mild vs. severe pneumonia is unexpected and raises questions about the validity of the study findings. In another study in pediatric patients with bacterial or viral CAP, syndecan-4 showed poor discriminatory power (AUROC ≈ 0.5) [14]. However, the viral pneumonia subgroup in this study was underrepresented (16 patients) compared to the bacterial subgroup (74 patients).…”
Section: Syndecan-4contrasting
confidence: 61%
See 1 more Smart Citation
“…The conflicting difference between higher syndecan-4 levels in mild vs. severe pneumonia is unexpected and raises questions about the validity of the study findings. In another study in pediatric patients with bacterial or viral CAP, syndecan-4 showed poor discriminatory power (AUROC ≈ 0.5) [14]. However, the viral pneumonia subgroup in this study was underrepresented (16 patients) compared to the bacterial subgroup (74 patients).…”
Section: Syndecan-4contrasting
confidence: 61%
“…Lipocalin-2 levels increase during infection and inflammation; lipocalin-2 plays a key role in innate immunity through interference with bacterial iron uptake [30]. In pediatric patients with bacterial and viral pneumonia, lipocalin-2 failed to discriminate between these groups (AUROC ≈ 0.5) [14]. Here, lipocalin-2 was studied in the same study as syndecan-4, which under-represented the viral pneumonia group.…”
Section: Lipocalin-2mentioning
confidence: 91%
“…After duplicate removal, the title and abstracts were manually sorted and matched according to the inclusion and exclusion criteria. A total of 16 articles were fully reviewed [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Afterward, details were extracted for each article as described in methods.…”
Section: Resultsmentioning
confidence: 99%
“…A total of eleven studies involved CRP [14,16,17,19,20,22,23,[25][26][27][28][29]. In all the studies analysing CRP as a diagnostic marker, the average CRP level was higher in the bacterial group than viral group [14,20,22,23,[25][26][27][28][29]. In an investigation by Esposito et al [20] the mean level of CRP was 32.2 mg/L in 74 bacterial CAP cases as compared to 9.4 mg/L from 16 viral CAP cases.…”
Section: Standard Biomarkers In Community-acquired Pneumonia C Reactimentioning
confidence: 99%
“…31 In this study, the CRP values were significantly higher among the coinfection group than others, which was similar to the results of previous reports. 20,21,[32][33][34] The optimal cutoff point for hs-CRP was 1.53 mg/dl (sensitivity 90%, specificity 56%), and the AUC for hs-CRP was 0.772, indicating this diagnostic value was valid. Although some authors were arguing that CRP is not useful in distinguishing coin-fected bacterial infections in patients with Rhinovirus community pneumonia, 26,35 other studies were confirming the ability to distinguish between viral and bacterial agents that cause pneumonia with CRP limit point > 0.8mg/dl.…”
Section: Discussionmentioning
confidence: 93%